2009
DOI: 10.1007/s11671-009-9312-z
|View full text |Cite
|
Sign up to set email alerts
|

New Method to Prepare Mitomycin C Loaded PLA-Nanoparticles with High Drug Entrapment Efficiency

Abstract: The classical utilized double emulsion solvent diffusion technique for encapsulating water soluble Mitomycin C (MMC) in PLA nanoparticles suffers from low encapsulation efficiency because of the drug rapid partitioning to the external aqueous phase. In this paper, MMC loaded PLA nanoparticles were prepared by a new single emulsion solvent evaporation method, in which soybean phosphatidylcholine (SPC) was employed to improve the liposolubility of MMC by formation of MMC–SPC complex. Four main influential factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The bulky structure and large surface area of AMB-NPs make them an excellent solubilizer, emulsifier, and bioavailable enhancer of hydrophobic drugs. 19,28 The NPs have high affinity to cells and can be rapidly internalized by these cells, and then AMB is gradually released from NPs in a sustained manner. 29 Our results suggested that PLGA-TPGS NPs were an excellent polymer carrier of hydrophobic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The bulky structure and large surface area of AMB-NPs make them an excellent solubilizer, emulsifier, and bioavailable enhancer of hydrophobic drugs. 19,28 The NPs have high affinity to cells and can be rapidly internalized by these cells, and then AMB is gradually released from NPs in a sustained manner. 29 Our results suggested that PLGA-TPGS NPs were an excellent polymer carrier of hydrophobic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome these side effects of MMC, and to obtain higher treatment efficacy, many attempts have been made to incorporate the drug in different delivery systems. These include intratumoral injection of MMC–dextran conjugates [Nomura et al., ], arterial chemoembolization with polyvinylalcohol or degradable starch microspheres [Rump et al., ; Shitara et al., ], and incorporation of MMC in polylactic acid nanoparticles [Hou et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous suspensions of biodegradable polyesters, e.g., PLA nanoparticles, are well known. [27,28] Suspensions of PLA nanoparticles are obtained as secondary suspensions, for example, by solvent displacement methods and emulsion, double emulsion and salting out methods. [29,30] The method selected is dependent on the size and loading efficiency required for different biomedical applications.…”
Section: Introductionmentioning
confidence: 99%